Impact of glycolysis inhibitor (2-DG) and oxidation and phosphorylation uncoupler (2,4-DNP) on brain metabolites - O. B. Shevelev; M. P. Moshkin (Вавиловский журнал генетики и селекции, 2018)
Deviations in brain metabolism are the result of longterm pathological processes, which finally are manifested as symptoms of Parkinson’s or Alzheimer’s diseases or multiple sclerosis and other neuropathologies, as for example diabetic neuropathy. A deficiency of available energy for brain cells under neurodegenerative diseases is either developed due to age-dependent underexpression of genes that encode glycolytic enzymes or induced due to the uncoupling of oxidation and phosphorylation that could be mediated by inflammatory cytokines. Since the activity of many enzymes is under the control of adenosine triphosphate (ATP) or cofactors, such as nicotinamide adenine dinucleotide (NADH) and nicotinamide adenine dinucleotide phosphate (NADPH), energy deficiency can cause metabolic changes in brain tissue. Some clinical studies using proton nuclear magnetic resonance spectroscopy (1H NMR spectroscopy) revealed metabolic changes in brain tissue in patients with neurodegenerative diseases. However, data from different authors are quite contradictory, probably because of the complex genesis of metabolic disorders. In the present study, we tested the hypothesis of multidirectional changes in metabolism under the impact of the oxidation and phosphorylation uncoupler 2,4-dinitrophenol (2,4-DNP) and under the impact of 2-deoxy-Dglucose (2-DG), blocking the access of glucose to the brain cells. 1H NMR spectroscopy showed that 2-DG leads to the predominance of excitatory (glutamine + glutamate) neurotransmitters over inhibitory ones (gamma-aminobutyric acid), and 2,4 DNP causes opposite effects. The biochemical mechanisms of the observed changes require a special study, but it can be noted that the ATP deficiency caused by inhibition of glycolysis and the ATP deficiency caused by the uncouplers are accompanied by differently directed changes in the intensity of the tricarboxylic acid cycle. These changes in the intensity of the Krebs cycle are correlated with differently directed changes in the balance of the exciting and inhibitory neurotransmitters. The obtained results show that 1H NMR spectroscopy can be an effective method of differentiated lifetime assessment of the available energy deficit caused by a general suppression of energy exchange in nerve cells or oxidation and phosphorylation uncoupling.